Assessment of in vitro cytotoxic and genotoxic activities of some trimethoprim conjugates - Bayulken, Devrim Guzel; Bostancioglu, R. Beklem; Koparal, A. Tansu; Tuylu, Berrin Ayaz; Dag, AYDAN; DAĞ, AYDAN; Benkli, KADRİYE; BENKLİ, KADRIYE (My University, 2018)
Trimethoprim, a commonly used antibacterial agent, is widely applied in the treatment of variety of infections in human. A few studies have demonstrated an extensive exposure of man to antibiotics, but there is still a lack of data for cytotoxic effects including nephrotoxicity, gastrointestinal toxicity, hematotoxicity, neurotoxicity and ototoxicity. The main purpose behind this study was to determine cytotoxic and genotoxic activities of trimethoprim (1), trimethoprim with maleic acid (2) and trimethoprim in conjugation with oxalic acid dihydrate (3). The cytotoxic effects of these three conjugates were elucidated by employing 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazoium bromide (MTT) assay using embryonic rat fibroblast-like cell line (F2408) and H-ras oncogene activated embryonic rat fibroblast-like cancer cell line (5RP7). Additionally, determination of genotoxic activity of these three compounds were studied by using cytokinesis blocked micronucleus assay (CBMN) in human lymphocytes. The results demonstrated that trimethoprim alone and its combination with other compounds are able to induce both cytotoxic and genotoxic damage on cultured cells (F2408, 5RP7, human lymphocytes).